HEAVY CONCRETE TO RESTORE CARRYING CAPACITY OF URBAN TRANSPORT FACILITIES - , Д. В. (Municipal economy of cities. Series: «Economy science», 2013)
Theoretical generalizations and solving practical tasks is to develop concrete increased resistance to activated binders for repair and restoration of artificial transport facilities provided by the use of chemically active components of the cement.